Relaparotomy After Cesarean Delivery: A Prospective Study (Journal of Dhaka Medical College, 2011)
The present study aimed at exploring the causes of re laparotomy following Caesarean section and to find out the pathway how to avoid these complications. This is a hospital based prospective study conducted in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh from August 2007 to August 2008. Bangladeshi pregnant women are at risk of serious complications during pregnancy and labor due to lack of antenatal, intra natal and postnatal care. DMCH is the largest referral hospital in Bangladesh and more than ten thousand patients admitted here each year with different pregnancy and child birth related complications. Among them, 54 puerpera needed re laparotomy after Caesarean section within 6 weeks of Caesarean Section. Of the 54 cases, 28 had primary PPH, 14 patients had secondary post-partum hemorrhage (PPH), 4 cases had puerperal sepsis and 3 women had wound dehiscence, and 5 cases had sub rectus hematoma. Irreversible hemorrhagic shock (12cases), cardio genic shock (1 case), not reversed from anesthesia (1 case), acute renal failure (3cases) and puerperal sepsis (1 case) were causes maternal death. It gave the overall case fatality rate was 33.33%. Obstetric patients who return to the operation theater face potential death. This study will help us to identify the risk situations where re laparotomy may be needed and due precautions and prevention may be taken as far as possible to avoid this complications following caesarean section and thereby reduce maternal mortality and morbidity. Key word: Cesarean section; laparotomy; maternal morbidity; maternal mortality; case fatality. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8583 J Dhaka Med Coll. 2011; 20(1) :57-62